2018
DOI: 10.4236/ojpm.2018.89025
|View full text |Cite
|
Sign up to set email alerts
|

The Patterns of Blood Groups and Its Association with Blood Donation in Saudi Arabia

Abstract: Background: Blood groups system has key importance for transfusion safety and clinical practice. Therefore, the objective of the present study was to evaluate the distribution of ABO blood groups and its association with blood donation in Saudi Arabia. Methodology: In this study, we collected information regarding blood donation from 715 Saudi volunteers living in the city of Hail, Northern Saudi Arabia. Data about blood donation were obtained from 715 Saudi volunteers living in the city of Hail. Results: The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The distribution of the RH blood group ABO blood group was significant different (P = 0.00). There is similarity to some extent if the results of the current study are compared with other studies, such as studies conducted in Saudi which showed that the ABO/RhD blood group distribution was O+>A+>B+>AB+>O->A->B->AB-and in Libyia was O+>A+ >B+ >O->A->AB+>B-> AB- (13) and also in Thailand and Australia, in which frequency was O+>B+>A+>AB+>O->B->A->AB-and O+>A+>B+>O->A->AB+>B->AB-respectively [13,15,20,27,28]. In other side, study carried out in Switzerland which stated that ABO/RhD blood group distribution was A+>O+>B+>A->O->AB+>B->AB- [25].…”
Section: Discussionmentioning
confidence: 75%
“…The distribution of the RH blood group ABO blood group was significant different (P = 0.00). There is similarity to some extent if the results of the current study are compared with other studies, such as studies conducted in Saudi which showed that the ABO/RhD blood group distribution was O+>A+>B+>AB+>O->A->B->AB-and in Libyia was O+>A+ >B+ >O->A->AB+>B-> AB- (13) and also in Thailand and Australia, in which frequency was O+>B+>A+>AB+>O->B->A->AB-and O+>A+>B+>O->A->AB+>B->AB-respectively [13,15,20,27,28]. In other side, study carried out in Switzerland which stated that ABO/RhD blood group distribution was A+>O+>B+>A->O->AB+>B->AB- [25].…”
Section: Discussionmentioning
confidence: 75%
“…Mixed ethnic population with considerable disparity of red blood cell antigens among blood donors and recipients exhibits a greater risk of alloimmunization in regular blood transfusion recipients (Alateeq et al., 2018; Alcantara et al., 2021). Literature shows several studies reporting the rate of ABO and RhD antigens in Saudi population (Abdullah, 2010; Alalshaikh et al., 2021; Alateeq et al., 2018; Alsuhaibani et al., 2015; Alzahrani et al., 2018; Saboor et al., 2020). Limited data of other most important antigens of the Rh blood group system including C, c, E and e and Kell blood group system, that is, K from Southwestern region of Saudi Arabia have been published (Alalshaikh et al., 2021; Halawani & Arjan, 2021); however, specifically no data are available from Samtah.…”
Section: Introductionmentioning
confidence: 99%
“…The distribution of blood group antigens varies significantly among different ethnicities. Mixed ethnic population with considerable disparity of red blood cell antigens among blood donors and recipients exhibits a greater risk of alloimmunization in regular blood transfusion recipients (Alateeq et al., 2018; Alcantara et al., 2021). Literature shows several studies reporting the rate of ABO and RhD antigens in Saudi population (Abdullah, 2010; Alalshaikh et al., 2021; Alateeq et al., 2018; Alsuhaibani et al., 2015; Alzahrani et al., 2018; Saboor et al., 2020).…”
Section: Introductionmentioning
confidence: 99%